Conversion of Glycerol to Dihydroxyacetone by Immobilized Whole Cells of Acetobacter xylinum - Nabe, Koichi (1979)
Enzymatic production of dihydroxyacetone (DHA) was studied by immobilization of the whole cells of acetic acid bacteria capable of oxidizing glycerol to DHA. Acetobacter xylinum A-9 cells immobilized in a polyacrylamide gel were selected as the most favorable enzyme preparation. The enzymatic properties of immobilized cells converting glycerol to DHA were investigated and compared with those of intact cells. The optimum pH for the immobilized cells was broad (4.0 to 5.5), whereas the intact cells had a narrow pH optimum at 5.5. The thermal stability of the immobilized cells was somewhat higher than that of the intact cells. Apparent K(m) values for glycerol with both intact and immobilized cells were about equal, 6.3 × 10(−2) to 6.5 × 10(−2) M. The complete conversion of glycerol to DHA was achieved within 40 h under optimum conditions, and pure crystalline DHA was readily isolated from the reaction mixture with over 80% yield.